AI Governance and Global Stability: Why U.S. Leadership Matters - Bhandari, Rajat; Bhandari, Shraddha (Journal of Current Social and Political Issues, 2025)
The global landscape is undergoing a profound transformation driven by artificial intelligence (AI), a technology that has the potential to reshape global power dynamics, economies, and societies. The United States (U.S.) has historically played a central role in guiding technological advancements, offering leadership that has prioritized ethical governance and global stability. Drawing a parallel to the U.S. leadership during the development of atomic weapons, this study emphasizes the necessity for the U.S. to take a proactive and responsible role in the governance of AI. Without U.S. leadership, the proliferation of AI risks falling into the hands of authoritarian regimes, such as China and Russia, whose use of AI for surveillance, censorship, disinformation, and military purposes could destabilize international norms and threaten democratic values. The study uses agency theory to argue that the global community must rely on the U.S. as a responsible agent to ensure AI technologies are used ethically and for the collective benefit of humanity. The paper also incorporates social comparison theory, technological determinism, and international relations realism to further illustrate the strategic and moral imperative of U.S. leadership in AI governance. By examining the historical context of U.S. leadership in managing disruptive technologies, this study highlights the urgent need for the U.S. to establish global AI governance frameworks that prioritize human rights, equity, and democratic values, countering the risks posed by authoritarian misuse of AI. Overall, the study employs a systematic meta-analysis, utilizing agency theory and complementary frameworks such as social comparison theory, technological determinism, and realism to analyze the U.S.'s role in global AI governance, drawing from peer-reviewed literature sourced from databases like Google Scholar, PubMed, and Web of Science, published between 2010 and 2025. The analysis reveals that U.S. leadership in AI prioritizes ethical development, transparency, and international collaboration, contrasting sharply with China and Russia’s authoritarian strategies focused on surveillance, militarization, and disinformation, underscoring the urgent need for U.S.-led global norms to ensure AI aligns with democratic values and fosters global stability.